A smooth compactification of the space of genus two curves in projective space: via logarithmic geometry and Gorenstein curves - Battistella, Luca; Carocci, Francesca (Arxiv, 2021)
We construct a modular desingularisation of $\overline{\mathcal{M}}_{2,n}(\mathbb{P}^r,d)^{\text{main}}$. The geometry of Gorenstein singularities of genus two leads us to consider maps from prestable admissible covers: with this enhanced logarithmic structure, it is possible to desingularise the main component by means of a logarithmic modification. Both isolated and non-reduced singularities appear naturally. Our construction gives rise to a notion of reduced Gromov-Witten invariants in genus two.
Version 1 vom 31. August 2020, Version 2 vom 30. Oktober 2020, Version 3 vom 10. September 2021
Gesehen am 06.10.2022